The Influence of Competence and Emotional Intelligence on Work Life Balance and Satisfaction Work as an Intervening Variable for Employees at the Community Health Center Binjai Highlands - Hana Niska Tafonao; Kiki Farida Ferine (International Journal of Economics, Management and Accounting (IJEMA), 2025)
This study aims to analyze the influence of competence and emotional intelligence on work-life balance with job satisfaction as a mediating variable among employees at Puskesmas Tanah Tinggi Binjai. Employing a quantitative approach with explanatory research design, data were collected through questionnaires from a total population of 80 employees and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results indicate that emotional intelligence has a significant effect on job satisfaction, and job satisfaction positively influences work-life balance. Competence does not affect job satisfaction but has a direct influence on the balance of work. Furthermore, emotional intelligence indirectly affects work-life balance through job satisfaction, while competence does not show a significant indirect effect via the same variable. This study highlights the importance of developing emotional intelligence and competence to enhance work-life balance in the healthcare sector work environment.